PENGARUH LAMA FERMENTASI MENGGUNAKAN Lactobacilus Plantarum AK1 TERHADAP KANDUNGAN SAPONIN DAN KUALITAS KIMIA DAUN TREMBESI (Sammanea saman): EFFECT OF FERMENTATION TIME USING Lactobacillus Plantarum AK1 ON SAPONIN CONTENT AND CHEMICAL QUALITY OF TREMBESI LEAVES (Sammaneasaman) - Prasetyo, Aris Budi; Sariri, Ahimsa Kandi; Windyasmara, Ludfia (Universitas Boyolali, 2023)
This study aims to determine the effect of duration time fermentation using Lactobacillus plantarum AK 1 on saponin content and chemical quality of trembesi leaves (Sammaneasaman). The fermentation treatments using three treatment duration time by 3, 9, and 15 days with each treatment replicated 4 times. There were 3 x 4 = 12 experimental units were obtained. The data obtained were analyzed using Completely Randomized Design Analysis (One-way ANOVA). The parameters observed aresaponin content, protein, fat, water content, ash, and carbohydrates. The result indicates that using Lactobacillus plantarum AK 1 bacteria for 3, 9 and 15 days duration time of fermentation had no effect on the saponin content and chemical quality of protein, fat, water and carbohydrates in trembesi leaves (Sammaneasaman).